SOCIO-CULTURAL AND SOCIO-PSYCHOLOGICAL POSTMODERNITY IN THE MOVIE WALL-E DIRECTED BY ANDREW STANTON - Aditya Chandra Nugroho; Merry Lapasau (INFERENCE: Journal of English Language Teaching, 2022)
This research has a purpose to analyze the theme elements inside the movie of WALL-E. The theme that is going to be analyzed are the socio-cultural and socio-psychological postmodernity. This research is designed by using the approach of qualitative argumentative research. The data for this research is collected directly from the movie itself, its screenplay and its novel adaptation. The form of the data collected is in narrative and descriptive text, dialogue, symbols and images. The result founds that the elements and themes of socio-cultural and socio-psychological postmodernity truly reigns the movie WALL-E; 1). The socio-cultural postmodernity depiction in this movie shows many aspects such as; the abrupt modern culture and technology, the modern world consumerism, the modern human relationship, and also the government negligence toward its own people. The portion of this theme is 54,8%. 2). The depiction of socio-psychological postmodernity in this movie shows the birth of the agent of change among the society and the abrupt modern world social awareness. The portion of this theme is 29,6%. 3). The pure postmodernity symbols (in a form of either the wordplay or the images used in the movie) that are also shown vividly has the portion of 15,6%. This means that the theme of socio-cultural postmodernity dominates the movie. But alas, due to the connection of every themes of the movie toward postmodern theme, in conclusion, the postmodernity is the theme that truly dominates the movie 100%.